Social Influences and Social Desirability on Recollections of Childhood Bullying - Bohart, Jaynee L (2021)
Parents and peers play important roles in shaping attitudes toward a variety of matters during adolescence. However, little research has investigated parental and peer influence on developing attitudes toward bullying. Further, few studies have looked at whether socially desirable responding (SDR) impacts self-reports in bullying research. To address these gaps in literature, the current study recruited college students from a mid-sized public university in the Rocky Mountain region of the United States to complete a survey. The survey assessed the participants’ past attitudes toward bullying, perceptions of their parents’ and peers’ influence on their attitudes, and bullying participant roles during their 7th and 8th grade years. The survey also assessed participants’ tendencies to respond in socially desirable ways. Results indicated that while participants reported both their parents and peers as significantly influential on their past attitudes, they perceived their parents as more influential and the two sources of influence were found to interact with one another. This interaction revealed that when parental influence is low, stronger peer influence is associated with weaker anti-bullying attitudes. Finally, a significant relationship between SDR and bully-victims were found, but results did not show that SDR was related to participants’ past attitudes or that bullying participant roles acted as a significant moderator. Implications, limitations, and future directions were discussed as well